Analisis Kemampuan Pemecahan Masalah Matematika Melalui Pendekatan Analogi dengan Bantuan Media Wordwall Pada Materi Bangun Datar di MI AL-Kautsar Durisawo - Yafita Arfina Mu’ti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze students' mathematical problem-solving abilities through an analogy approach with the aid of Wordwall media on the topic of plane figures at MI Al-Kautsar Durisawo. This study used a descriptive qualitative approach to describe the mathematical problem-solving abilities of fifth-grade students at MI Al-Kautsar Durisawo through an analogy approach with the aid of Wordwall media. Data were collected through tests, interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of techniques and sources, as well as verification through member checks with students and teachers. The results showed that the analogy approach was effective in systematically improving students' mathematical problem-solving abilities. Wordwall media was proven to facilitate the visualization of abstract concepts, making learning more engaging, interactive, and increasing enthusiasm for learning. It showed by the students' test results, which showed an average score of 81.41. The test results showed that 15.63% were in the high category, 67.74% in the medium category, and 18.75% in the low category. High-ability students demonstrated strong understanding and critical thinking, while students with medium and low abilities still required additional guidance. Overall, this approach had a positive impact on class engagement, learning responses, and the development of students' thinking skills.